Long-term prognostic benefit of beta-blockers use after discharge in patients with Tako-Tsubo syndrome. (25th November 2020) - Jamhour-Chelh, K; Raposeiras-Roubin, S; Nunez-Gil, I; Abu-Assi, E; Aritza Conty, D; Vedia, O; Almendro-Delia, M; Sionis, A; Martin-Garcia, A.C; Corbi-Pascual, M; Martinez-Selles, M; Uribarri, A; et al.
Abstract: Background: Tako-tsubo Syndrome (TS) seems to be associated with a catecholamine-mediated mechanism. However, the impact of beta-blockers (BB) in-hospital and after discharge still remain uncertain. Objectives: The purpose of the study was to examine whether BB use after discharge in patients with TS, was associated with lower long-term mortality and recurrence. Methods: Using a national multicentre large-scale inpatient database (RETAKO Registry), we analysed patients with a definitive TS diagnosis. Results: A total of 970 patients were analysed (568 with BB therapy and 402 no-BB therapy). After discharge and over a median of follow-up of 1.1 years, treatment with BB have no shown prognostic effectiveness in terms of mortality and TS recurrence in unadjusted and adjusted Cox analysis (HR 0.86; 95% CI: 0.59 to 1.27; and 0.95; 95% CI: 0.57–1.13, respectively). Conclusions: This data suggests that use of beta-blockers after hospital discharge has not shown long-term prognostic benefit in patients with Tako-tsubo Syndrome. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Retako webpage was funded by a non-conditioned Astrazeneca scholarship.